2019
DOI: 10.1016/j.jcmgh.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

A High-Calorie Diet Aggravates Mitochondrial Dysfunction and Triggers Severe Liver Damage in Wilson Disease Rats

Abstract: Background & Aims In Wilson disease, ATP7B mutations impair copper excretion into bile. Hepatic copper accumulation may induce mild to moderate chronic liver damage or even acute liver failure. Etiologic factors for this heterogeneous phenotype remain enigmatic. Liver steatosis is a frequent finding in Wilson disease patients, suggesting that impaired copper homeostasis is linked with liver steatosis. Hepatic mitochondrial function is affected negatively both by copper o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 62 publications
4
49
0
1
Order By: Relevance
“…Feeding a WD to the LPP rat led to an earlier onset of the disease at approximately 3 weeks and a significantly more severe course of the disease. Liver mitochondria of WD-fed LPP rats were severely affected, with separated inner and outer membranes, excessive matrix condensation and swollen cristae [226]. This study further underlines the important influence of dietary intake on liver mitochondrial morphology and function.…”
Section: Influence Of Nafld-inducing Diets On Liver Mitochondrial Morsupporting
confidence: 58%
See 1 more Smart Citation
“…Feeding a WD to the LPP rat led to an earlier onset of the disease at approximately 3 weeks and a significantly more severe course of the disease. Liver mitochondria of WD-fed LPP rats were severely affected, with separated inner and outer membranes, excessive matrix condensation and swollen cristae [226]. This study further underlines the important influence of dietary intake on liver mitochondrial morphology and function.…”
Section: Influence Of Nafld-inducing Diets On Liver Mitochondrial Morsupporting
confidence: 58%
“…In a recent study, a WD was applied in the LPP rat model of Wilson's disease [226]. Wilson's disease is a genetic disorder of copper homeostasis that is frequently associated with liver steatosis and is, therefore, often misdiagnosed as NAFLD [227,228].…”
Section: Influence Of Nafld-inducing Diets On Liver Mitochondrial Mormentioning
confidence: 99%
“…HSP60, an important mitochondrial stress protein, has been shown to play key roles in the protein synthesis, folding, and delivery of misfolded proteins to proteolytic enzymes in the mitochondrial matrix (Tatsuta 2009, Haynes & Ron 2010, Hu & Liu 2011, Marino Gammazza et al 2018. Recent studies have showed that mitochondrial stress is associated with mitochondrial dysfunction and metabolic disorders such as hepatic steatosis, insulin resistance, and type 2 diabetes (Venojarvi et al 2008, Hu & Liu 2011, Comert et al 2019, Einer et al 2019. ER and mitochondria have partially overlapping functions, and there is strong crosstalk between the two organelles to regulate hepatic steatosis (Haynes & Ron 2010, Hu & Liu 2011, Ghemrawi et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…5 Thus, insufficient autophagy may contribute to the initiation and progression of WD, in line with the observation that obesity, a state in which autophagy is inhibited due to the excess of nutrients, aggravates WD. 7 Of note, a minimal amount of copper is required for the initiation of the autophagic cascade, as copper binds to and stimulates the kinase activity of the pro-autophagic kinases, Unc-51 like autophagy activating kinases 1 and 2 (ULK1, ULK2). Complete depletion of copper hence blocks autophagy.…”
Section: Extending the Mode Of Action Of Triethylenetetramine (Trientmentioning
confidence: 99%